1992
DOI: 10.1096/fasebj.6.12.1521737
|View full text |Cite
|
Sign up to set email alerts
|

Studies of intestinal stem cells using normal, chimeric, and transgenic mice 1

Abstract: The mouse intestinal epithelium represents a continuous developmental system. Its four principal differentiated cell types--enterocytes, goblet, enteroendocrine, and Paneth cells--are derived from a common multipotent stem cell located near the base of monoclonal crypts. Members of these four lineages undergo rapid and perpetual renewal along an anatomically well-defined pathway. The gut epithelium provides a unique mammalian model for studying the biological features of stem cells (e.g., their ability to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(81 citation statements)
references
References 1 publication
4
77
0
Order By: Relevance
“…Stem cells located in the crypts are a source for continuous and rapid renewal of the epithelium (Gordon 1989). Earlier studies in mice have shown that each small intestinal crypt produces an average of 13-16 new cells/hr (Gordon et al 1992). Cell differentiation and cell migration are coupled events in the gut.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cells located in the crypts are a source for continuous and rapid renewal of the epithelium (Gordon 1989). Earlier studies in mice have shown that each small intestinal crypt produces an average of 13-16 new cells/hr (Gordon et al 1992). Cell differentiation and cell migration are coupled events in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Cell differentiation and cell migration are coupled events in the gut. The epithelial cells differentiate and mature during migration from the crypt to the apex of the villus or surface epithelial cuff (Lipkin 1985;Gordon 1989;Gordon et al 1992). This process is completed in a few days, which makes the mammalian intestinal epithelium a unique model system for studying cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation is restricted to a subpopulation of enterocytes located in the crypts at the bases of the villi (Babyatsky and Podolsky, 1991). Mitotic activity ceases as cells migrate out of the crypts, and there is a concomitant increase in the expression of a number of di erentiated gene products (Gordon et al, 1992;Traber, 1994). Di erentiated enterocytes are removed by the process of apoptosis which occurs throughout the villus and by exfoliation which occurs at the villus tip (Gavrieli et al, 1992;Hall et al, 1994;Chandrasekaran et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian small intestine is lined by a highly specialized epithelium that displays a wide-ranging yet tightly regulated functional diversity along its cephalo-caudal axis (13). The functional diversity is linked to a continuous renewal process in which stem cells located near the base of crypts produce transit-amplifying cells that ultimately differentiate into four principal cell types.…”
mentioning
confidence: 99%